Sulfate-catalyzed denitrifying anaerobic methane oxidation process mediated by Methanobacterium sp. from digestion sludges - Shibo Fu; Wen-Bo Nie; Xin Tan; Xiaoming Wang; Lili Li; Guo-Jun Xie (Water Research, 2026)

Lactiplantibacillus plantarum ZJ316 synergizes with tryptophan diet to modulate gut microbiota and metabolite profiles in mice - Qingqing Zhou; Yingying Zhou; Lu Li; Kening Fu; Shibo Liu; Ping Li; Qing Gu (Food Bioscience, 2026)

A novel failure mode and effects analysis model enhanced with systems theory and artificial intelligence for dynamic positioning systems in offshore operations - Shibo Wu; Baoping Cai; Yiqin Fu; Yixin Zhao; Xiaoyan Shao; Chuntan Gao (Ocean Engineering, 2026)

Floc-granule microbial symbiosis drives DNRA in anammox bacteria via cross-feeding for complete autotrophic nitrogen removal - Yulong Yang; Wen-Bo Nie; Xin Tan; Lili Li; Chenhui Yu; Shibo Fu; Ke-Di Peng; Yi Luo; Xiao Ran; Zhihong Zheng; Jin Xu; Jun Li; et al. (Chemical Engineering Journal, 2025)

The risk assessment for metal(loid)s in soil-slag mixing systems: Coupling sequential extraction, leaching tests, and in vitro bioaccessibility assays - Zelin Xu; Damao Xu; Jingnan Ma; Jiayi Wang; Shibo Yan; Rongbing Fu; Yanshan Cui (Journal of Hazardous Materials, 2025)

Effluent organic matter facilitates anaerobic methane oxidation coupled with nitrous oxide reduction in river sediments - Chenhui Yu; Qiang He; Wen-Bo Nie; Tanglong Zhang; Hao Wu; Yulong Yang; Shibo Fu; Xin Tan; Yi Chen (Water Research, 2025)

Spatiotemporal evolution and improvement pathways of sustainable entrepreneurship efficiency: Alleviating environmental and employment pressures - Shibo Fu; Songyu Jiang; Shengjie Wang; Xiaoe Wang (Journal of Environmental Management, 2025)

Human reliability analysis of offshore high integrity pressure protection system based on improved CREAM and HCR integration method - Yang Yu; Shibo Wu; Yiqin Fu; Xiaowei Liu; Qingze Zeng; Hongyu Ding; Yu Pan; Yuke Wu; Hao Guo; Yuheng Yang (Ocean Engineering, 2024)

Modeling temperature change and water migration of unsaturated soils under seasonal freezing-thawing conditions - Zhiguo Wang; Shibo Fu; Xuefeng Zhao; Wei Jiang; Gongliang Liu; Dong Li; Hanbing Qi (Cold Regions Science and Technology, 2024)

A study on the impact of the carbon emissions trading policy on the mining industry based on Porter hypothesis - Yaxin Zhang; Shibo Zeng; Qiaosheng Wu; Junyi Fu; Tongping Li (Resources Policy, 2023)

Production and Biological Effects of Extracellular Vesicles from Adipose-Derived Stem Cells Were Markedly Increased by Low-Intensity Ultrasound Stimulation for Promoting Diabetic Wound Healing - Yi Zheng; Peng Xu; Chuqiao Pan; Yikai Wang; Zibo Liu; Yahong Chen; Chuhsin Chen; Shibo Fu; Ke Xue; Qimin Zhou; Kai Liu (Stem Cell Reviews and Reports, 2023)

Local application of triamcinolone acetonide-conjugated chitosan membrane to prevent benign biliary stricture - Tao Wang; Shibo Zhang; Lianmin Wang; Kun Su; Zhiyi Tang; Haiyu He; Yanmei Shi; Yaqiong Liu; Mengyao Zheng; Wen Fu; Sheng Hu; Xiaowen Zhang; et al. (Drug Delivery and Translational Research, 2022)

The inhibition of CFTR in the descended testis of SD rats with unilateral cryptorchidism induced by di-(2-ethylhexyl) phthalate (DEHP) - Xiangliang Tang; Dian Li; Tianxin Zhao; Shibo Zhu; Xiaofeng Gao; Rui Zhou; Fuming Deng; Wen Fu; Wei Jia; Guochang Liu (Environmental Science and Pollution Research, 2022)

CFRP Strengthening and Rehabilitation of Inner Corroded Steel Pipelines under External Pressure - Jianxing Yu; Weipeng Xu; Yang Yu; Fei Fu; Huakun Wang; Shengbo Xu; Shibo Wu (Journal of Marine Science and Engineering, 2022)
The objective of this study was to investigate the performance of pipelines repaired with carbon-fibre-reinforced polymer (CFRP) under external pressure. The repaired pipeline experienced defects in terms of thinning of its local inner wall. The three-dimensional finite element method was used to analyse the collapse pressure of repaired pipes with internal corrosion defects. The traction–separation law and interlaminar damage criterion were applied to simulate the collapse process of repaired pipes. The results show that the collapse pressure of the composite-repaired pipe increased and the CFRP significantly reduced the strain in the defect region. It was observed that the ovality of the corrosion defect region was reduced and that the repair effectiveness mainly depended on the length, thickness, and interlayer cohesion.